Anomalous low-temperature “post-desorption” from solid nitrogen - Savchenko, E.V.; Khyzhniy, I.V.; Uyutnov, S.A.; Ponomaryov, A.N.; Gumenchuk, G.B.; Bondybey, V.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Anomalous low-temperature post-desorption (ALTpD) from the surface of nominally pure solid nitrogen pre-liminary irradiated by an electron beam was detected for the first time. The study was performed using a combi-nation of activation spectroscopy methods — thermally stimulated exoelectron emission (TSEE) and spectrally resolved thermally stimulated luminescence (TSL) — with detection of the ALTpD yield. Charge recombination reactions are considered to be the stimulating factor for the desorption from pre-irradiated α-phase solid nitrogen.